Criminal Liability of Legal Persons According to Albanian Judicial Practice - Lulzim Karini; Gjon Buxhuku (European Scientific Journal, ESJ, 2026)
The work addresses the criminal liability of legal persons in Albanian criminal law, aiming for a balanced analysis of the normative framework and its application in judicial practice. The study begins with an examination of the provisions of the 1995 Criminal Code, which laid the foundations for the criminal liability of legal persons, and continues with an analysis of Law No. 9754/2007, which is a lex specialis in this field in Albania.The work primarily focuses on the practice of the Supreme Court, particularly analyzing the conditions under which a criminal offense is considered committed in the name and for the benefit of a legal person, the role of representatives and governing bodies in establishing the link between individual acts and the criminal liability of the subject, and the criminal sanctions applied by courts, including both primary and supplementary penalties.In conclusion, the study offers a critical assessment of the effectiveness of the existing legal framework and judicial practice, highlighting specific issues and drawing conclusions about the need for clarification and further improvement in the treatment of the criminal liability of legal persons by the courts, as well as the necessity for legislative changes.